PENGARUH PROFESIONALISME DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Inspektorat Kabupaten Bengkalis) - Rizky M.Fachrul; Rasuli muhammad; Putra Agri Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of professionalism and independence on job satisfaction and audit quality at the Bengkalis Regency Inspectorate. The population in this study were 40 employees at the Bengkalis Inspectorate, all of which were used as samples with saturated sampling technique. Data were analyzed using path analysis using Warp.PLS software version 7.0. The results of the study concluded that professionalism and independence as well as job satisfaction had a significant positive effect on audit quality at the Bengkalis Regency Inspectorate. Then employee job satisfaction is able to fully mediate the influence between professionalism and independence on audit quality at the Bengkalis Regency Inspectorate. Based on the results of the path analysis, it is known that 14% of professionalism can directly explain the variance of audit quality, independence can explain 20% of the variance, while job satisfaction can explain up to 38% of the audit quality variance. R square analysis on audit quality which is influenced by professionalism, independence, and job satisfaction is 43% with moderate strength category, Q square understanding of taxation is 0.430 which means that professionalism, independence, and job satisfaction are able to predict the value of audit quality well.Keywords: Independence, job satisfaction, audit quality, professionalism, inspectorate